2021
DOI: 10.1016/j.str.2021.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure and resistance landscape of M. tuberculosis MmpL3: An emergent therapeutic target

Abstract: Highlights d Cryo-EM structure of M. tuberculosis MmpL3 determined at 3.0 Å resolution d An LMNG molecule within the periplasmic cavity suggests the TMM export pathway d Comprehensive structural mapping of resistance-conferring MmpL3 variants d Genome-mined MmpL3 mutations indicate minimal preexisting resistance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 92 publications
(123 reference statements)
0
36
0
Order By: Relevance
“…MmpL3 inhibitors bind to the transmembrane domains (TM) of MmpL3 and are likely to block the proton relay and thus the TMM transport [14,18,19,21,23,24]. The mechanism of MmpL3-dependent transport of TMM and the mode of action of the inhibitors are still difficult to apprehend, mainly because of the absence of an in vitro transport assay.…”
Section: Figure 1 Overall Structure Of Mmpl3msm and Construct Designmentioning
confidence: 99%
See 2 more Smart Citations
“…MmpL3 inhibitors bind to the transmembrane domains (TM) of MmpL3 and are likely to block the proton relay and thus the TMM transport [14,18,19,21,23,24]. The mechanism of MmpL3-dependent transport of TMM and the mode of action of the inhibitors are still difficult to apprehend, mainly because of the absence of an in vitro transport assay.…”
Section: Figure 1 Overall Structure Of Mmpl3msm and Construct Designmentioning
confidence: 99%
“…In the studies describing MmpL3 crystal structures, both M. smegmatis [19] and E. coli [17] were used to produce recombinant MmpL3. Furthermore, MmpL3 purification was achieved using n-Dodecyl-ß-d-Maltopyranoside (DDM) for MmpL3Msm and Lauryl Maltose Neopentyl Glycol (LMNG) for MmpL3Mtb [21] as detergents. The present study was undertaken to expand the repertoire of useful detergent(s) to extract, purify and stabilize MmpL3Msm, particularly warranted to further decipher the biological/biochemical function of MmpL3 and for subsequent structural investigations.…”
Section: Figure 1 Overall Structure Of Mmpl3msm and Construct Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cryogenic electron microscopy (Cryo-EM) structure of Mycobacterium tuberculosis Mmpl3 (PDB ID ) was reported recently by Adams et al 19 Although the resolution of the structure had an acceptable value of 3 Å, one of the major issues we faced with the structure was defining the binding site space for our molecules of interest. As the reported structure was not in a ligand bound state, the known binding residues were used to define the binding site.…”
Section: Methodsmentioning
confidence: 99%
“…The N -substituted indoles were docked into a Mtb MmpL3 homology model ,, and their binding poses were compared to those of pyrrole 2 and SQ109 (a comparison of the best-scoring binding poses of both SQ109 and 7j is reported in Figure S1, while the best scoring binding poses of 5f , 7a , 7h , and 7m are reported in Figure S3). The molecular docking study suggested that the introduction of lipophilic aliphatic groups of varying sizes at the N1 position could lead to a better interaction of the compounds with the hydrophobic binding pocket of MmpL3 (Figure ).…”
mentioning
confidence: 99%